Auditing and Professionalism at the Graduate Level. - Robertson, Jack C.; Smith, Charles H. (The Accounting Review, 1973)
Abstract This article presents information on the results of a survey which reflects the views of practicing auditors on the issue of appropriate content for a second course in auditing at the university level. The results of the survey constitute some thoughts on an appropriate direction for auditing and professional education at the graduate level. A questionnaire was sent in batches to participating coordinators in 19 offices representing 16 different CPA firms in Texas. These coordinators distributed the instrument randomly to their respective audit staff personnel. In the analyses of responses which follow the mean importance response was used to rank the topics in order of descending importance, educators may thus be able to compare their judgments with the opinions of practitioners. The mean time assignments for each topic may give educators a starting point for design of the desired auditing course. For purposes of this study, the desired course was viewed as being a part of the fifth year of accounting study by reason of its coverage of material beyond the introductory theory and elementary principles of auditing.